The Influence of Storytelling for Speaking Ability at Senior High School - Dewi Maharani; Dzul Rachman (Departement of Mathematics Education, 2024)
This study aims to determine the impact of storytelling as a teaching tool in Islamic high schools. Since they will have numerous opportunities to learn English effectively, this study also focused on selecting tenth-grade students as participants. If students who are told stories have an impact on their ability to communicate, the researcher would like to investigate this. The purpose of this study is to evaluate the effectiveness of the storytelling approach as a teaching strategy in secondary Islamic institutions. The purpose of this study is to determine whether the narrative method may help tenth-grade students at MAN 1 Samarinda become more proficient speakers. Pre- and post-tests were employed in the quantitative research design to gauge how well storytelling improved students' speaking abilities. Written assessments, group discussions, and questionnaires were the study's instruments. Students were required to create short stories based on their everyday experiences for the written exam. During group presentations, students read the stories they had written in front of the class, and their performance was evaluated on their fluency, pronunciation, grammar, vocabulary, idea structure, expression, and gestures. Students' responses about using the storytelling method to improve their speaking abilities were gathered through questionnaires. The findings demonstrated that pupils' speaking abilities were improved via storytelling. After engaging in narrative exercises, students demonstrated gains in vocabulary, pronunciation, and fluency. Additionally, this strategy was well received by pupils, the majority of whom reported feeling more driven and intrigued. The purpose of this literature review is to expand readers' knowledge about the function of storytelling in the classroom, specifically about students' development as more fluent communicators. For this investigation, a quantitative research approach will be used.